Assessment of Financial Performances of Indian Firms Involved in Domestic and Overseas Mergers & Acquisitions - Banerjee, Sirsanath (2016)
In order to increase competitiveness, portfolio expansion, minimize business risk, enter unchartered territories, make full use of the economies of scale, face the challenges of globalization and achieve competitive advantage over other companies, an unprecedented wave of mergers & acquisitions has engulfed the world in the past few decades. Today, India is on the world map for being a hotbed for mergers & acquisitions with transactions worth US$ 38.1 billion (IBEF, 2015) recorded in 2014 which is a massive rise from the $2.2 billion worth of M&A transactions booked in 1998. With such growth figures in the merger & acquisition scene in India, a study on the impact on performance of the acquiring firm will be of great interest to researchers as well as the industry in order to shape the future of mergers & acquisitions in India. Furthermore, as M&A activities in India can be clearly distinguished between overseas & domestic, research is required to compare the impact that each of them has on the financial performance of acquiring firms. With these research objectives in mind, the researcher examined the financial performance of the acquiring firms that made domestic & overseas acquisitions during the financial years of 2007-08 and 2008-09 by studying their financial ratios for a period of 5 years pre-merger and 5 years post-merger and comparing the same using inferential statistical tools. The researcher compared 23 financial ratios on a sample of 68 firms (36 domestic acquisitions and 32 overseas acquisitions) over a period of 10 years thereby analyzing a total of 15,640 data points. The results suggest that while mergers & acquisitions reduce expenses and material costs of acquiring firms, there is evidence to prove that they negatively impact the profitability, liquidity, debt coverage and cash flow indicators of the acquiring firm and there are mixed results pertaining to the effect of merger & acquisitions on the management efficiency ratios of the acquiring firm. In terms of difference in performance between domestic and overseas acquisitions, the researcher found that the predominant decline in financial performance was slightly higher in case of domestic acquisitions as compared to overseas acquisitions.